2020
DOI: 10.1186/s12929-020-00651-0
|View full text |Cite
|
Sign up to set email alerts
|

Fasting to enhance Cancer treatment in models: the next steps

Abstract: Short-term fasting (STF) is a technique to reduce nutrient intake for a specific period. Since metabolism plays a pivotal role in tumor progression, it can be hypothesized that STF can improve the efficacy of chemotherapy. Recent studies have demonstrated the efficacy of STF in cell and animal tumor models. However, large-scale clinical trials must be conducted to verify the safety and effectiveness of these diets. In this review, we reexamine the concept of how metabolism affects pathophysiological pathways. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 140 publications
(190 reference statements)
0
19
0
Order By: Relevance
“…The benefits of fasting for cancer and other diseases have been carefully reviewed elsewhere (Nencioni et al, 2018;de Cabo and Mattson, 2019;Caffa et al, 2020;Tajan and Vousden, 2020;Zhang J. et al, 2020). Pre-clinical (Lee et al, 2012;Brandhorst et al, 2015;Wei et al, 2017;de Cabo and Mattson, 2019;Caffa et al, 2020), and early clinical studies (Caffa et al, 2020;de Groot et al, 2020), show benefits for coupling fasting or fasting-mimicking diets (FMDs) with chemotherapy and/or endocrine therapy, including enhanced treatment efficacy, reduce side effects and the prevention of drug resistance.…”
Section: Combining Fasting and Hyperthermia To Constrain Cancer Cell Diversity And Adaptability During Chemotherapy Strikesmentioning
confidence: 99%
“…The benefits of fasting for cancer and other diseases have been carefully reviewed elsewhere (Nencioni et al, 2018;de Cabo and Mattson, 2019;Caffa et al, 2020;Tajan and Vousden, 2020;Zhang J. et al, 2020). Pre-clinical (Lee et al, 2012;Brandhorst et al, 2015;Wei et al, 2017;de Cabo and Mattson, 2019;Caffa et al, 2020), and early clinical studies (Caffa et al, 2020;de Groot et al, 2020), show benefits for coupling fasting or fasting-mimicking diets (FMDs) with chemotherapy and/or endocrine therapy, including enhanced treatment efficacy, reduce side effects and the prevention of drug resistance.…”
Section: Combining Fasting and Hyperthermia To Constrain Cancer Cell Diversity And Adaptability During Chemotherapy Strikesmentioning
confidence: 99%
“…Another proposed method to target the metabolism of tumor cells is through short term dietary fasting. Fasting diets are currently in clinical trial to enhance chemotherapy efficacy and reduce toxicity however there is also evidence they may slow tumor progression [235]. In the fasting state IGF-1, a promoter of EMT, is inhibited, and clinical trials are underway to investigate if tumor progression can be inhibited [235].…”
Section: Targeting Metastasis Through Adipose Tissue-tumor Interactionsmentioning
confidence: 99%
“…Fasting diets are currently in clinical trial to enhance chemotherapy efficacy and reduce toxicity however there is also evidence they may slow tumor progression [235]. In the fasting state IGF-1, a promoter of EMT, is inhibited, and clinical trials are underway to investigate if tumor progression can be inhibited [235]. Obesity induces lung neutrophilia leading to increased breast cancer lung metastasis through GM-CSF and IL-5 signaling.…”
Section: Targeting Metastasis Through Adipose Tissue-tumor Interactionsmentioning
confidence: 99%
“…In this regard, despite being debatable and largely rejected in some standard oncology practices, the therapeutic effects of short-term fasting during anticancer therapy should be discussed. [56][57][58][59] Clinical studies confirmed that when conducted exclusively under medical supervision and after careful assessment of the patient's condition (early-stage cancer with no signs of severe weight loss, diabetes, sarcopenia, cachexia or eating disorders), short-term water-only fasting just before and after radiotherapy could enhance the cytotoxic effects on the tumor cells at many levels. 56 Such an additional metabolic therapy contributes to the increased stress on oncogene-driven tumor cells during chemo/ radio therapy-it reduces the amount of their main source of energy and building blocks for growth, DNA repair and poliferation, gradually weakening all anti-apoptotic signaling pathways maintained by nutrition.…”
Section: Tumor Cells Radioresistance As a Function Of Complex Factors-a Large Number Of Hidden Pro-survivalmechanisms In Tumor Cells Limimentioning
confidence: 98%